Thermo-mechanical stresses distribution on bone drilling: Numerical and experimental procedures - Fernandes, Maria G (2019)
In bone drilling, the temperature and the level of stresses at the bone tissue are function of the drilling parameters. If certain thresholds are exceeded, irreversible damages may occur on the bone tissue. One of the main challenges in the drilling process is to control the associated parameters and even more important, to avoid the surrounding tissue damage. In this study, a dynamic numerical model is developed to determine the thermo-mechanical stresses generated during the bone drilling, using the finite element method. The numerical model incorporates the geometric and dynamic characteristics involved in the drilling processes, as well the developed temperature inside the material. The numerical analysis has been validated by experimental tests using polyurethane foam materials with similar mechanical properties to the human bone. Results suggest that a drill bit with lower drill speed and higher feed rate can reduce the strains and stresses in bone during the drilling process. The proposed numerical model reflected adequately the experimental results and could be useful in determination of optimal drilling conditions that minimise the bone injuries.